2006
DOI: 10.1348/014466505x90136
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential predictors of traumatic reactions to psychotic episodes

Abstract: The study provides further evidence that negative reactions to psychotic episodes are relatively common. Clinicians may wish to assess for such symptoms. The study extended these findings by identifying a number of candidate psychological predictors of PTSD reactions such as perceptions of uncontrollability and absence of support. Prospective longitudinal studies are required to test the causal significance of these factors. More broadly, the findings indicate that traumatic stress in response to intra-psychic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
1
31
1
1
Order By: Relevance
“…The IES consists of two dimensions experienced in the past 7 days, a 7 item intrusion subscale (internal reliability α = 0.85) and an 8 item avoidance subscale (α = 0.85). Studies typically consider scores of 0-8 as 'sub-clinical', 9-25 'mild reaction to trauma', 26-43 'moderate', and 44+ 'severe' (e.g., Chisholm, Freeman & Cooke, 2006). Condon & Corkindale, 1998): This 19 item self-report questionnaire provides a measure of mother-infant attachment (α = 0.78).…”
Section: Face/voice Stimulimentioning
confidence: 99%
“…The IES consists of two dimensions experienced in the past 7 days, a 7 item intrusion subscale (internal reliability α = 0.85) and an 8 item avoidance subscale (α = 0.85). Studies typically consider scores of 0-8 as 'sub-clinical', 9-25 'mild reaction to trauma', 26-43 'moderate', and 44+ 'severe' (e.g., Chisholm, Freeman & Cooke, 2006). Condon & Corkindale, 1998): This 19 item self-report questionnaire provides a measure of mother-infant attachment (α = 0.78).…”
Section: Face/voice Stimulimentioning
confidence: 99%
“…Three of the studies focused on forensic samples. In the first, PTSD symptoms were significantly associated with higher perceptions of power of the persecutor, inability to cope, thinking the persecution to be deserved, and lower ratings of control over the situation (Chisholm, Freeman, & Cooke, 2006). In the second, Calvert, Larkin, and Jellicoe-Jones (2008) showed that negative cognitions about the self correlated positively, moderately, and significantly with distress related to delusions and delusion-related preoccupation, and negative cognitions about the world correlated positively, moderately, and significantly with paranoia.…”
mentioning
confidence: 94%
“…In addition, these positive psychotic symptoms may cause psychological distress in the patients themselves or their significant others. Chisholm, Freeman, and Cooke (2006) found a positive association between the experience of psychotic episodes and traumatic stress in a sample of remitted psychiatric patients. Pang et al (2002) reported that the presence of delusions and hallucinations in Alzheimer's patients was correlated with reports of higher levels of psychological stress among Chinese and European American caregivers.…”
Section: Introductionmentioning
confidence: 85%